2019
DOI: 10.1371/journal.pone.0210835
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-associated procoagulant phospholipid and tissue factor activity in multiple myeloma

Abstract: Multiple myeloma (MM) patients have increased risk of developing venous thromboembolism, but the underlying mechanisms and the effect on the coagulation system of the disease and the current cancer therapies are not known. It is possible that cancer-associated extracellular vesicles (EV), carrying tissue factor (TF) and procoagulant phospholipids (PPL) may play a role in thrombogenesis. The aim of this study was to perform an in-depth analysis of procoagulant activity of small and large EVs isolated from 20 MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…Such conclusion was supported by the direct correlation measured between the percentage of CD38 hi EV and malignant plasma cells in the BM [70]. Notably, the presence of CD38 and CD39 on EV isolated from BM of MM patients has been recently confirmed by electron microscopy analysis [72].…”
Section: Cd38 Expression On Extracellular Vesicles: Another Mechanismmentioning
confidence: 68%
“…Such conclusion was supported by the direct correlation measured between the percentage of CD38 hi EV and malignant plasma cells in the BM [70]. Notably, the presence of CD38 and CD39 on EV isolated from BM of MM patients has been recently confirmed by electron microscopy analysis [72].…”
Section: Cd38 Expression On Extracellular Vesicles: Another Mechanismmentioning
confidence: 68%
“…Transmission Electron Microscopy (TEM) was performed to detect and confirm vesicular CD9 + structures in the EV pellets. TEM was performed as previously described [ 35 ]. Briefly, five microliters of pooled EV pellets were mounted for 30 seconds on carbon-coated, glow discharged 400 mesh Ni grids (SPI Supplies, Chester, PA, USA), stained with one drop 1% ( w / v ) phosphotungstic acid (PTA) pH 7.0 (Ted Pella, Caspilor AB, Lindingö, Sweden), and then dry-blotted using filter papers.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that EVs have an important role in different steps of the metastatic process (Colombo et al, 2019). Due to their pro-coagulant activity, EVs could lead to platelet activation and polymerization of fibrinogen to fibrin, which in turn would enhance MM dissemination by protecting the malignant plasma cells in the circulation, favoring their seeding to distant sites and pre-conditioning the metastatic niche with platelet-derived cytokines (Labelle et al, 2014; Remiker and Palumbo, 2018; Nielsen et al, 2019). It has also been shown that MM-EVs contribute to neo-angiogenesis by inducing endothelial cell proliferation and formation of new blood vessels (Liu et al, 2014; Wang et al, 2016; Li et al, 2019; Zarfati et al, 2019).…”
Section: Multiple Myeloma: a Metastatic Disease That Depends On The Bmentioning
confidence: 99%